MUSIC FESTIVALS IN MODERN ITALY DURING THE COVID-19 PANDEMIC - PONOMARENKO, Olena (Studia Universitatis Babes-Bolyai Musica, 2022)
This study analyses one of the complex problems of modern artistic discourse – the functioning of a music festival as a special form of intercultural dialogue and its integration into a modern cultural medium. The article reveals the issues of the relationship of its components, such as the conditions for the implementation of intercultural communication in the context of a music festival; the morphological space of the multi-layer score of this artistic phenomenon; forms of intercultural communication, and sociocultural constraints associated with the Covid-19 pandemic. The purpose of this study was to analyze the music festival as one of the forms of polyculture dialogue and its functioning in the new realities of the Covid-19 pandemic. In this regard, both theoretical (semantic analysis) and practical (comparative analysis) research methods were used. As a result of the study, it was proven that a music festival as one of the forms of intercultural dialogue allows realizing different semantic levels of culture, enriches spirituality, and contributes to the consolidation of representatives of different cultures, leading to a constructive solution of the problems of artistic discourse; it was revealed that during the Covid-19 pandemic, not all genre and stylistic forms could be realized, due to the difficult situation of socio-cultural isolation; a classification of new formats for holding music festivals was proposed, which take into account the current conditions for its functioning in the context of the Covid-19 pandemic. The practical significance of this study is that its results can be used for further analysis of the mechanisms of functioning and broadcasting of a polyphonically complex score of a music festival.